Dietary purslane (Portulaca oleracea L.) promotes the growth performance of broilers by modulation of gut microbiota - Cong Wang; Qing Liu; Fengchun Ye; Hongbo Tang; Yanpeng Xiong; Yongfei Wu; Luping Wang; Xuanbiao Feng; Shuiyin Zhang; Yongmei Wan; Jianhua Huang (AMB Express, 2021)
Abstract Purslane is a widespread wild vegetable with both medicinal and edible properties. It is highly appreciated for its high nutritional value and is also considered as a high-quality feed resource for livestock and poultry. In this study, Sanhuang broilers were used to investigate the effect of feeding purslane diets on the growth performance in broilers and their gut microbiota. A total of 48 birds with good growth and uniform weight were selected and randomly allocated to four treatment groups A (control), B, C and D. Dietary treatments were fed with basal diet without purslane and diets containing 1%, 2% and 3% purslane. The 16S rDNA was amplified by PCR and sequenced using the Illumina HiSeq platform to analyze the composition and diversity of gut microbiota in the four sets of samples. The results showed that dietary inclusion of 2% and 3% purslane could significantly improve the growth performance and reduce the feed conversion ratio. Microbial diversity analysis indicated that the composition of gut microbiota of Sanhuang broilers mainly included Gallibacterium, Bacteroides and Escherichia-Shigella, etc. As the content of purslane was increased, the abundance of Lactobacillus increased significantly, and Escherichia-Shigella decreased. LEfSe analysis revealed that Bacteroides_caecigallinarum, Lachnospiraceae, Lactobacillales and Firmicutes had significant differences compared with the control group. PICRUSt analysis revealed bacteria mainly enriched in carbohydrate metabolism pathway due to the additon of purslane in the diet. These results suggest that the addition of purslane to feed could increase the abundance of Lactobacillus in intestine, modulate the environment of gut microbiota and promote the metabolism of carbohydrates to improve its growth performance. This study indicates that the effect of purslane on the growth-promoting performance of broilers might depend on its modulation on gut microbiota, so as to provide a certain scientific basis for the application of purslane in the feed industry.